AKT1 Phosphorylates FDX1 to Promote Cuproptosis Resistance in Triple‐Negative Breast Cancer - Zicheng Sun; Huazhen Xu; Guanming Lu; Ciqiu Yang; Xinya Gao; Jing Zhang; Xin Liu; Yongcheng Chen; Kun Wang; Jianping Guo; Jie Li (Advanced Science)
Abstract Cuproptosis, a recently defined copper‐dependent cell death pathway, remains largely unexplored in tumor therapies, particularly in breast cancer. This study demonstrates that triple‐negative breast cancer (TNBC) bears a relatively elevated copper levels and exhibits resistance to cuproptosis. Mechanistically, copper activates the AKT signaling pathway, which inhibits ferredoxin‐1 (FDX1), a key regulator of cuproptosis. AKT1‐mediated FDX1 phosphorylation not only abrogates FDX1‐induced cuproptosis and aerobic respiration but also promotes glycolysis. Consequently, the combination of AKT1 inhibitors and the copper ionophores synergistically alleviate TNBC tumorigenesis both in vitro and in vivo. In summary, the findings reveal a crucial mechanism underlying TNBC resistance to cuproptosis and suggest a potential therapeutic approach for TNBC.